Detection and identification of Trichophyton tonsurans from clinical isolates and hairbrush samples by loop‐mediated isothermal amplification system. Issue 9 (19th February 2016) - Yo, Ayaka; Yamamoto, Mikachi; Nakayama, Takako; Ishikawa, Jun; Makimura, Koichi
Abstract: Since the 1990s, there have been reports of the spread of dermatophytosis caused by Trichophyton tonsurans among contact sports athletes in several countries, including Japan. This study was performed to develop a loop‐mediated isothermal amplification (LAMP) system for rapid and accurate detection and identification of T. tonsurans from clinical isolates or hairbrush samples for diagnosis and to prevent the spread of infection. A specific primer set was prepared by comparing the whole genome sequence of T. tonsurans with those of six other closely related dermatophytes. After confirming the sensitivity and specificity of this system, LAMP assay was performed using 37 clinical samples obtained from three healthy volunteers and 24 judo athletes. A total of 155 fungal isolates (56 strains of various standard fungi, 96 identified T. tonsurans isolates, three hairbrush‐cultured isolates from judo athletes) and 37 hairbrush samples (34 samples from 24 judo athletes, and three samples from three healthy volunteers) were used for culture and LAMP assay, respectively. The assay showed no cross‐reactivity to standard strains other than T. tonsurans . The detection limit was 100 copies of DNA template per tube. All of the 96 T. tonsurans isolates were amplified, and all samples from healthy volunteers showed negative results. Four of the 34 hairbrush samples obtained from judo athletes showed positive results in LAMP assay, and two of the four were positive in both culture and LAMP assay. We developed a rapid LAMP system with high specificity and sensitivity for diagnosis of T. tonsurans infection.